INTANGIBLE FACTORS AND THEIR INFLUENCE ON THE PLANNING AND IMPLEMENTATION OF THE REGIONAL DEVELOPMENT STRATEGIES - A. Nazarov (Вестник университета)
The article examines the main directions of regional development strategies, taking into account the possibilities of using non-material factors. Based on the analysis of regional features of the use of non-material factors of development, the main directions of regional development strategies are formulated. The developed directions can be used by regional administrations and the business community in developing a balanced and effective regional development strategy that ensures the competitiveness of Russian regions.